NeuroSwipe: Crowdsourcing the Brain–Citizen Science in Neuroimaging Research - Ana Mirza-Davies; Sonya Foley; Derek Jones; Judith Harrison (BJPsych Open)
Aims: Large-scale neuroimaging projects rely on automated pipelines to reconstruct white matter tracts from diffusion MRI (dMRI) data. However, these reconstructions are not always accurate and often require labour-intensive manual review to identify artefacts. To address this challenge and extend the reach of science engagement beyond traditionally accessible groups, we developed NeuroSwipe: a web-based platform designed to involve the public in evaluating the quality of dMRI data. This initiative also aimed to enhance participants’ understanding of brain imaging techniques and the scientific process, fostering broader public involvement in research.